ERK1/2-HNF4α axis is involved in epigallocatechin-3-gallate inhibition of HBV replication - Wang Zi-yu; Li Yu-qi; Guo Zhi-wei; Zhou Xing-hao; Lu Mu-dan; Xue Tong-chun; Gao Bo (Acta Pharmacologica Sinica, 2020)
Epigallocatechin gallate (EGCG), a major polyphenol in green tea, exhibits diverse biological activities. Previous studies show that EGCG could effectively suppress HBV gene expression and replication, but the role of EGCG in HBV replication and its underlying mechanisms, especially the signaling pathways involved, remain unclear. In this study we investigated the mechanisms underlying EGCG inhibition on HBV replication with a focus on the signaling pathways. We showed that EGCG (12.5−50 μM) dose-dependently inhibited HBV gene expression and replication in HepG2.2.15 cells. Similar results were observed in HBV mice receiving EGCG (25 mg· kg−1· d−1, ip) for 5 days. In HepG2.2.15 cells, we showed that EGCG (12.5−50 μM) significantly activate ERK1/2 MAPK signaling, slightly activate p38 MAPK and JAK2/STAT3 signaling, while had no significant effect on the activation of JNK MAPK, PI3K/AKT/mTOR and NF-κB signaling. By using specific inhibitors of these signaling pathways, we demonstrated that ERK1/2 signaling pathway, but not other signaling pathways, was involved in EGCG-mediated inhibition of HBV transcription and replication. Furthermore, we showed that EGCG treatment dose-dependently decreased the expression of hepatocyte nuclear factor 4α (HNF4α) both at the mRNA and protein levels, which could be reversed by pretreatment with the ERK1/2 inhibitor PD98059 (20 μM). Moreover, we revealed that EGCG treatment dose-dependently inhibited the activity of HBV core promoter and the following HBV replication. In summary, our results demonstrate that EGCG inhibits HBV gene expression and replication, which involves ERK1/2-mediated downregulation of HNF4α.These data reveal a novel mechanism for EGCG to inhibit HBV gene expression and replication.